Right To Recall Political Representatives: Legal Audit of Article 85 Passage (1) Letter C Of Regulation Number 22 of 2003 And Article 12 Letter B Of Regulation Number 31 Of The Year 2002 - Ngateman Ngateman; Endang Kusuma Astuti (Jurnal Indonesia Sosial Sains, 2023)
The overall game plans for pardoning people from the DPR are contained in Article 22 B of the 1945 Constitution of the Republic of Indonesia read "Individuals from the DPR can be excused from office, the circumstances and systems for which are controlled in regulation" and afterward managed further in Regulation Number 17 of 2014 concerning Individuals' Consultative Get together, Individuals' Delegate Gathering, Territorial Agent Chamber, and Local Individuals' Agent Committee (MD3) and Regulation Number 2 of 2008 concerning Ideological groups. In the legal literature in Indonesia which regulates dismissal and replacement between members of the DPR, political parties have a great role in it. Where these guidelines are contained in Article 239 section (2) letter d of Regulation Number 17 of 2014 concerning Individuals' Consultative Gathering, Individuals' Agent Committee, the Territorial Agent Board, and the Local Nation's Agent Chamber expressed that ideological groups can choose individuals from Individuals' Agent Board who comes from the ideological group itself to be excused. Regarding legal regulations like this, it can be said that political parties have an active role in monitoring members of the DPR.